The Role of Imam Shamil in the Muridism Movement and Its Strengthening - Jabarov, Rashad (Scholarya Demo Journal of Ruby, 2020)
The North Caucasus began a struggle during Russia’s occupation of these territories. This movement is recorded in history as Muridism. Overall, muridism went down in history as the main ideology of resistance to the Russian occupation under the leadership of Sheikh Mansur. The highlanders of Dagestan and Chechnya succeeded in uniting under the flag of Muridism. Therefore, we can say that Muridism played an important role in the struggle of the Caucasian peoples against the Russian occupation, as well as in the consolidation of local peoples. This movement is recognized as an example of the resistance of the Caucasian peoples around the Islamic ideas against the Russians. It had a positive effect on the consciousness of the Caucasian peoples and the preservation of their religion despite all the pressure. One of the most important figures in this movement was Imam Shamil. Being bold, strong and educated, Imam Shamil was a real example of human will and courage. He is a historical figure uniting the small peoples of Dagestan and Chechnya into one state. He fought for his independence and freedom for many years. A number of factors contributed to the continuation and expansion of Sheikh Shamil’s struggle. Most notably, massacres committed by Russia during its occupation of the region, as well as its policy against the national and moral values of the peoples, expanded the scope of Sheikh Shamil’s activities. Sheikh Shamil’s role in the formation of Muridism was that his ideas of Muridism created foundation to consolidate the masses. With the spread of these ideas, people both joined the ideological struggle and were engaged in the systematic resistance movement. Muridism also had a significant impact on the weakening of ethnic and tribal conflicts between the Muslim peoples of the North Caucasus, including partly the South Caucasus. This is evident from the fact that Imam Shamil’s envoys represented many nations. Considering all these aspects, the period of Sheikh Shamil’s leadership in the Muridism movement has scholarly significance.